Edmund Booth : deaf pioneer - Lang, Harry G. (Book collections on Project MUSE., 2004)
Annotation "Born in 1810, Edmund Booth epitomized virtually everything that characterized an American legend of the 19th century. He taught school in Harford, CT, then went west to Anamosa, Iowa, where he built the area's first frame house. He left in 1849 to travel the Overland Trail on his way to join the California Gold Rush. After he returned to Iowa in 1854, he became the owner and editor of the Anamosa Eureka, the local newspaper. Edmund Booth fit perfectly the mold of the ingenious pioneer of 19th-century America, except for one unusual difference - he was deaf."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved